Burden and Social Support of Informal Caregivers in Palliative Care: Correlational Study Between Variables - Dalkirane, Mateus Meira; Silva, Lucilene L.; Banaco, Roberto A.; Miyazaki, Eduardo S. (Perspectivas em Análise do Comportamento, 2022)
Having a patient under Palliative Care (PC) impacts the Informal Caregiver’s (IC) routine. This study’s objectives are to identify correlations between Burden, Quality of Life (QoL) and Social Support of IC of patients under palliative care. This descriptive and correlational study’s sample is made up of 30 ICs in a high-complexity hospital and the data were collected through the scales: MOS-SSS (Medical Outcomes Study – Social Support Survey); QASCI (Informal Caregiver’s Burden Evaluation Questionnaire); SF-36 (Short Form Health Survey) and a sociodemographic questionnaire. A means of 67,5% of the participants scored high social support. The lowest means for QoL were for role-physical and role-emotional. Burden was negatively and weakly or moderately correlated to most of QoL domains. Burden was negatively and moderately correlated to social support regarding the tangible domain. Between Social Support and QoL the correlations were positive and weak or moderate. Vitality and mental health were correlated to every social support domain. The role of IC alters their routine and they may experience hardships dealing with such role. The buildup of tasks to which the caregiver lacks behavioral repertoire may help explain the reported burden.